Production of platelets in vitro in functionalised 3-dimensional scaffolds mimicking the bone marrow niche - Holly R. Foster; Maria Colzani; Guenaelle Bouet; Daniel Howard; Christian A. Di Buduo; Nicole Müller-Sienerth; Amie K. Waller; Yi Sun; Natalia Davidenko; Jennifer H. Shepherd; Thomas Moreau; Amanda L. Evans; et al. (Haematologica)
The safety, quality and supply of donor-derived platelet units intended for transfusion have improved over the past decades but significant problems still remain. In vitroderived platelets offer a possible alternative but up-scaling production is hindered by our limited understanding of thrombopoiesis (the release of platelets by their mother cell, the megakaryocyte [MK]). Here, we have developed an integrated strategy aiming to mimic ex vivo the bone marrow physiological niche that promotes thrombopoiesis by mature MKs. The screening of a panel of 259 recombinant transmembrane proteins derived from cells known to promote platelet production through direct contact with MKs enabled us to show that ACVR1B, CRTAM, MUCEN and BTN1A1 improve platelet production from either cord blood- (ACVR1B) or pluripotent stem cells-derived (CRTAM, MUCEN and BTN1A1) MKs. Using two different methodologies, we functionalise either collagen- or silkbased 3-dimensional scaffolds and confirm increased functional platelet production by up to two-fold. This unbiased approach has allowed us to identify novel proteins whose role in platelet formation was previously unknown and highlights the potential gain of recreating the MK niche to allow in vitro platelets to become a viable alternative for transfusion.